City Ceremonies in Burdur Cumhuriyet Square - Özyıldıran, Güler (ICONARCH International Congress of Architecture and Planning, 2017)
Burdur is a small scale Anatolian city which has only one central square, and its all borders are in the walking distance. Hence, the address of all national holidays, memorial days, local festivals and other ceremonies is its main square called Cumhuriyet Square, and activities in the Square affect the whole city. Cumhuriyet Square was constructed as the new city center after the construction of the first railway station and the railway street in 1936. Since then, the Square has three significant periods; 1) a circular square design with a circular pool 2) a circular square with an Ataturk Monument by sculptor Şadi Çalık 3) a rectangular square with ceremony platform and Republic Monument by designer and sculptor Yavuz Görey. Nowadays, there are various discussions to change the Square again. In this study, the uses of Burdur Cumhuriyet Square for city ceremonies are examined from past to present. The main resources are photography archive of Burdur Governorship and Burdur Municipality, and the city yearbooks. It is seen that the three different design of the square affected the practices of the ceremonies.